The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1097/igc.0000000000000774
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Small Interfering RNA Targeting YKL-40 Gene on the Proliferation and Invasion of Endometrial Cancer HEC-1A Cells

Abstract: YKL-40 targeting siRNA specifically blocks the activity of YKL-40 in human EC HEC-1A cells, resulting in tumor suppression. This indicates that YKL-40 might serve as a potential small molecule target in the treatment of EC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…Therefore, the HEC‐1A cell line was selected for subsequent studies. It was observed that small interfering RNA (siRNA) targeting YKL‐40 (si YKL‐40 ) could inhibit the proliferation, migration, and invasion of HEC‐1A cells (Li et al, 2016). It was also found that YKL‐40 was upregulated in EC and was correlated with the poor prognosis (Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the HEC‐1A cell line was selected for subsequent studies. It was observed that small interfering RNA (siRNA) targeting YKL‐40 (si YKL‐40 ) could inhibit the proliferation, migration, and invasion of HEC‐1A cells (Li et al, 2016). It was also found that YKL‐40 was upregulated in EC and was correlated with the poor prognosis (Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In gastric cancer, GATA6 has been shown to cooperate with other TFs, such as KLF5, to promote cancer development [ 34 , 35 ]. In CRC, GATA6 and Krüppel-like factor 5 (KLF5) have been implicated in the regulation of cancer stem cell characteristics and chemoresistance [ 36 , 37 ]. Signal transducer and activator of transcription 3 (STAT3) is a TF involved in various cellular processes, including cell growth, differentiation, and survival.…”
Section: Discussionmentioning
confidence: 99%
“…It is also involved in the regulation of malignancy in various tumors. YKL-40 interacts with a variety of extracellular matrix components and with invasive and metastatic processes of tumor cells in lung cancer, cholangiocarcinoma, endometrial cancer, and other malignancies [ 56 58 ]. YKL-40 is an independent risk factor for the occurrence and development of various tumors [ 59 ] and has been used as a marker of tumor growth and inhibition of tumor-cell apoptosis [ 60 ].…”
Section: Discussionmentioning
confidence: 99%